Eco-telhados: efeito das variações de formas e materiais na temperatura, volume e qualidade da água coletada - Munhos, Matheus Marinho; Silva, Alexandre Marco da (International Workshop for Innovation in Safe Drinking Water, 2022)
The presence of corrugated fiber cement roofs is great in several cities in Brazil, being one of the main roof coverings in Brazil. This research aimed to study the different dispositions of corrugated fiber cement tiles, being rotated 90° and with mortar barriers in relation to the quality of the water collected, the temperature and the amount of water retained for the purpose of contributing to the delay of surface runoff. The study methodology was through in loco data collection. The data were treated statistically to evaluate the correlation of results regarding temperature changes and similarities in water quality. It was found that over time the fiber cement tiles were less and less releasing physicochemical particles in the water, and that the changes in the dispositions did not influence the temperature. Tiles rotated by 90º showed higher water retention, making them an appropriate type for use in delaying surface runoff.